The impact of right atrium and left atrium reverse remodeling for functional regurgitation of atrioventricular valve among patients who were underwent ablation for atrial fibrillation. (3rd October 2022) - Nemoto, N; Samejima, Y; Takenaka, H; Yaguchi, T; Kameda, Y; Shimizu, T; Sahara, N; Takenaka, H; Nagashima, Y; Anzai, H
Abstract: Background: Atrial fibrillation (AF) is a risk factor of Regurgitation of Atrioventricular Valve and Regurgitation of Atrioventricular Valve is improved after ablation for AF. However, Mechanism of improvement of Tricuspid regurgitation (TR) and Mitral regurgitation (MR) after ablation for AF were unclear. Methods: The one hundred fifty-seven cases consecutive patients who were underwent ablation for persistent AF were examined in this study. These patients were performed Holter ECG and Echocardiography 6 months after ablation for persistent AF. The area of the Right Atrium (RA), Left Atrium (LA), diameter of the tricuspid valve anulus and Mitral valve annulus, were measured by echocardiography at before and 6 months after ablation for AF. The reverse remodeling index (RRI) was defined as divided post area of RA and LA by pre area of RA and LA. The Improved group was defined as one or more than regurgitation grade improvements. Results: TR improved in 56 cases (35.7%) of 157 cases and MR improved in 25 (16.6%) cases of 157 cases. The ratio of improved TR was significantly higher than ratio of improved MR (p<0.01). The difference in tricuspid annulus diameter before and after ablation for AF was significantly longer in TR improved group than in TR non-improved group. (4.9±5.3 mm vs 1.6±5.4 mm, p<0.01). The RRI of RA in TR improved group was significantly smaller than in TR non-improved group (0.73±0.19 vs 0.89±0.26 p<0.01). The difference in mitral annulus diameter before and after ablation for AF was not significant differences between MR improved group and MR non-improved group. The RRI of LA in MR improved group was significantly smaller than in MR non-improved group (0.79±0.22 vs 0.90±0.25 p<0.01). The RRI of RA was significantly smaller than RRI of LA among patients who were able to maintain sinus rhythm after ablation for persistent AF (0.79±0.23 vs 0.85±0.24 p=0.04). Conclusion: Reverse remodeling of RA was higher than Reverse remodeling of LA among patients who were able to maintain sinus rhythm after ablation for persistent AF and Reverse remodeling of RA and LA were important factors of improvement of TR and MR after ablation for persistent AF. These results considered to be the cause why the improvement rate of TR was higher than the Improvement rate of MR after persistent AF. Funding Acknowledgement: Type of funding sources: None.